Aspectos éticos relacionados ao processo de comunicação efetiva durante pandemia COVID-19: revisão integrativa - Silva Falcão , Bruna Caroline; Costa de Almeida, Jocelha Maria; Torres dos Santos, Adriana; Lima da Silva, Elza; Portela Silva Coutinho, Nair; Barros Fonseca, Lena Maria (Nursing Edição Brasileira, 2021)
Objective: Investigate the production of literature on the communication of the health team with patients and families during the COVID-19 pandemic. Method: This is an integrative review carried out in the VHL, PubMed and Scopus databases, using the health science descriptors (DeCS): Coronavirus, Bioethics and Communication. Results: 139 articles were obtained, with 6 articles selected for analysis of this review. The most common findings were: challenges in the communication process, especially among the most vulnerable populations, such as oncology, palliative care and intensive care unit patients; at the other end, strategies aimed at mitigating this problem, such as alternative methods of communication, which include a video component. Conclusion: Effective communication was compromised during the COVID-19 pandemic, requiring the creation of protocols based on ethical and bioethical parameters according to the values of each society.